2017
DOI: 10.1111/his.13412
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Phox2b immunohistochemical stain in neural crest tumours and non‐neural crest tumours in paediatric patients

Abstract: Phox2b was a specific and sensitive marker for pNT and PCC/PG, especially useful for identifying NB-UD often lacking TH. Our study also presented a composite rhabdomyosarcoma/neuroblastoma of neural crest origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…The effects of PHOX2B mutations on neuroblastoma, their associations with other well‐described molecular alterations, with prognosis and potential therapeutic options, continue to be explored. The role of PHOX2B immunostain in the diagnosis of neuroblastoma has also been described recently in several studies with high specificity and sensitivity …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The effects of PHOX2B mutations on neuroblastoma, their associations with other well‐described molecular alterations, with prognosis and potential therapeutic options, continue to be explored. The role of PHOX2B immunostain in the diagnosis of neuroblastoma has also been described recently in several studies with high specificity and sensitivity …”
Section: Discussionmentioning
confidence: 87%
“…Recently, several studies have looked at the utility of PHOX2B immunostain as a way to distinguish peripheral neuroblastic tumours from other small blue cell tumours, and it was demonstrated that PHOX2B has extensive nuclear expression in all neuroblastic and sympathetic nervous tumours, and it is negative in small blue cell tumours as Ewing sarcoma, desmoplastic small round blue cell tumour, hepatoblastoma and alveolar rhabdomyosarcoma . In one of these studies Hung et al .…”
Section: Introductionmentioning
confidence: 99%
“…IHC using anti-Phox2b antibody has been validated for clinical uses at our CLIA-certified laboratory as previously described. 10…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear Phox2b expression was uniformly strong in undifferentiated, poorly differentiated, and differentiating neuroblastoma cells and became more variable in maturing and mature ganglion cells and pheochromocytoma/paraganglioma cells. 10…”
Section: Introductionmentioning
confidence: 99%
“…Neuroblastoma cells are typically positive for neural antibodies (eg, neuron-specific enolase, synaptophysin, chromogranin A, NB84, and S-100 protein) [6,7], but these antibodies are not specific to neuroblastoma [8,9]. Tyrosine hydroxylase (TH) was the most widely used sympathoadrenal marker specific for neuroblastoma, but its sensitivity was insufficient (84%) [10,11]. The protein known as paired-like homeobox 2b (PHOX2B) has recently attracted attention as a sensitive and specific marker for neuroblastoma.…”
Section: Introductionmentioning
confidence: 99%